Effect of Organic and Inorganic Compounds on the Conductivity of Salt Solutions - Safitri, Wulan Dwi; Wardana, Dian; Ramadhan, Dwi Sapri; Fahmi, Jam'an; Zubir, Moondra; Purba, Sunita Karin; Puandra, Esti Miska; Siregar, Nurdin (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
This study examines the effects of selected organic and inorganic compounds on the electrical conductivity of salt solutions. Organic substances (sugar, coffee, tea, and a surfactant-based cleaner) and inorganic additives (ammonium chloride in cough medicine, povidone–iodine, and carbonated beverage) were mixed with salt solutions at varying concentrations to evaluate their influence on ion availability and mobility. The results show that conductivity increases proportionally with salt concentration, confirming that ion content is the primary factor governing charge transport. Inorganic ionic additives significantly enhanced conductivity by releasing additional ions into the solution, whereas non-ionic organic compounds consistently reduced conductivity at low salt levels by diluting ionic species and hindering ion mobility. Conductivity in organic mixtures increased only when salt concentration became dominant. These findings highlight the contrasting mechanisms of organic and inorganic additives in modifying electrolyte behavior and provide useful insight for chemistry education and simple electrochemical analysis.